Intimate partner violence, family court, and assessment : a qualitative study of the experiences of women's advocates : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in Psychology at Massey University, Palmerston North, New Zealand - Culver, Krystal (Massey University, 2015)
Intimate Partner Violence (IPV) is a pervasive problem throughout New Zealand. Approximately a third of all women will experience some form of abuse from their partner in their lifetime. Literature on IPV highlights the difficulties these women face when they enter the Family Court system and the lack of understanding regarding the dynamics of IPV. Of particular concern are those women who undergo a psychological assessment as part of the custody dispute. The Family Court has posited the movement to collaborative parenting may outweigh the need to keep women and children safe. Consequently, women may not only be re-victimised, but both their safety, and the safety of their children, could be at risk. The purpose of this study was to provide a greater understanding of women’s advocates experiences of issues of IPV, Family Court, and psychological assessment in New Zealand. Four advocates from Women’s Refuge were interviewed and a thematic analysis conducted. Four superordinate themes emerged from participants’ accounts: process difficulties, conflict, lack of expertise and gender-based issues, while a fifth theme of cultural differences emerged from one of the participants. These experiences were supported by the existing literature, and added valuable knowledge from a New Zealand context. Unexpected issues also arose, including the difficulty women with children face in being granted the right to relocate. This will help form the basis of continued research into the area, with the aim of gaining a more discerning picture of key issues that arise for women who have experienced IPV and who are embattled in a custody dispute in the Family Court.
Keywords: Family courts; Intimate partner violence; Abused women; Services for; Women's shelters; New Zealand